Veganism sentiments and preferences among Muslims - Mohd Zaki, Muhammad Nasrullah; Jamaludin, Mohammad Aizat; Mohd Nor, Nur Suriya; Azlan, Aishah (UPM Press, 2021)
Veganism has become a significant lifestyle which is being religiously practiced by people from across the globe as their routine. To date, the Muslims also followed suit with the trend of veganism in the quest of practicing a healthy lifestyle. Nonetheless, concerns arise on the degree of acknowledgement by the Islamic teachings on such diets which advocate for omitting animal products in one’s daily meal. Therefore, this paperwork seeks to identify the elements of veganism from the viewpoints of various perspectives of Muslims, based on their sentiments and personal preferences in order to examine the relevance of veganism as a lifestyle to be exercised by Muslims. Research data were collected from secondary sources which includes journals, books, papers and internet resources to retrieve information on veganism, vegetarianism and the Islamic theme regarding the issue. This research is important because it will resolve the existing conflict to understand whether the practice of veganism is present in Islam or otherwise. Two elements of veganism are animal rights and vegan diet. The concept of veganism is not existed in Islamic tradition but Islam has its own concept and practices on animal rights. Meanwhile, vegan diet is accepted to be practiced by Muslims as long as according to Islamic rulings.